Compositional variation in early‐life parenting structures alters oxytocin and vasopressin 1a receptor development in prairie voles (Microtus ochrogaster). (29th June 2021) - Rogers, Forrest D.; Freeman, Sara M.; Anderson, Marina; Palumbo, Michelle C.; Bales, Karen L.
Abstract: Paternal absence can significantly alter bio‐behavioural development in many biparental species. This effect has generally been demonstrated by comparing the development of offspring reared under biparental care with those reared by a single mother. However, studies employing this design conflate two significant modifications to early‐life experience: removal of father‐specific qualities and the general reduction of offspring‐directed care. In the socially monogamous prairie vole ( Microtus ochrogaster ), the experience of paternal absence without substitution during development inhibits partner preference formation in adulthood, a hallmark of social monogamy, in females and males. Employing alloparents as substitutes for fathers, our previous work demonstrated that paternal absence affects pair‐bond formation in female offspring via reduced quantity of care, although it affects pair‐bond formation in male offspring by means of a missing paternal quality (or qualities). Here, we present evidence that paternal absence (with and without alloparental substitution) may alter the ontogeny of neural oxytocin receptor (OXTR) and/or vasopressin 1a receptor (AVPR1a) distribution in male and female prairie voles. Compared to biparentally reared controls (BPC), male offspring reared in mother only (MON) and maternal‐plus‐alloparental (MPA) conditions show lower densities of OXTR in the central amygdala; and MPA males show lower densities of OXTR in the caudate putamen and nucleus accumbens. Early‐life experience was not associated with differences in AVPR1a density in males. However, MON and MPA females show greater densities of AVPR1a in the medial amygdala than BPC; and MPA females show greater densities of AVPR1a in the ventromedial nucleus of the hypothalamus. We also demonstrate with corticosterone concentrations that MON and MPA offspring are not differentially susceptible to a stressor (ie, social isolation) than BPC offspring. These findings suggest that paternal absence, although likely not a salient early‐life stressor, has neuroendocrine consequences for offspring, some of which may affect partner preference formation. Abstract : Paternal absence can significantly alter bio‐behavioural development in many biparental species, an effect that has generally been demonstrated by comparing the development of offspring reared under biparental care with those reared after removal of the father. Here, we demonstrate that paternal absence, with or without allopartental substitution, significantly alters oxytocin and vasopressin 1a receptor development in prairie voles ( Microtus ochrogaster ). We suggest that some of these neuroendocrine changes may affect partner preference formation, a hallmark of social monogamy.